2014
DOI: 10.1080/00397911.2013.837186
|View full text |Cite|
|
Sign up to set email alerts
|

Anticancer Activity of Pyrazole via Different Biological Mechanisms

Abstract: In the past few years pyrazole derivatives have attracted increasing attention because of their numerous potential pharmacological applications. Changes in their structure have offered a high degree of diversity that has proven useful for the development of new medicinal agents with improved potency and less toxicity. This review focuses on the recent developments in pyrazole along with their structure-activity relationship (SAR), particularly for anticancer activity. The review covers SAR for active pyrazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 90 publications
0
16
0
1
Order By: Relevance
“…[2] Noteworthy, pyrazoles were proved to possess potent anticancer activity. [9][10][11] One of the reported anticancer pyrazoles which induced apoptosis via Caspase-3 activationdependent pathway was the reported phenyldiazenyl-1Hpyrazoles-3,5-diamine derivative B. [10] Based on these findings, we found that it is interesting to hybridize triazoloquinoxaline scaffold by pyrazole moieties (c.f.…”
Section: Introductionmentioning
confidence: 88%
“…[2] Noteworthy, pyrazoles were proved to possess potent anticancer activity. [9][10][11] One of the reported anticancer pyrazoles which induced apoptosis via Caspase-3 activationdependent pathway was the reported phenyldiazenyl-1Hpyrazoles-3,5-diamine derivative B. [10] Based on these findings, we found that it is interesting to hybridize triazoloquinoxaline scaffold by pyrazole moieties (c.f.…”
Section: Introductionmentioning
confidence: 88%
“…[10,11] They have been found to induce apoptosis, caspase activation, cause DNA intercalation, inhibit tubulin polymerization and autophagy in various cancer cells, [12][13][14][15][16][17] Moreover, these compounds have exerted anticancer effects through inhibition of various receptors/enzymes/proteins involved in cancer cell division and growth. [8] Thus, it is evident that 3,5-diaryl pyrazolines can provide structural outlines for further anticancer drug development. Substituted 1,3-cyclopentadiones having structural framework (O=CÀ C(R)À C=O), which includes but not limited to 1,3-indanediones, thaizolidine-2,4-dione (TZD), phthalimides and pyrrolidine-2,5-diones (succinimides) have appealed to biologists and medicinal chemists since a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer activity of pyrazolines reviewed by various authors revealed that N‐substituted pyrazolines have exhibited antiproliferative and antitumor effects in vivo and in vitro (Figure ). Recent literature showcases the potent cytotoxic activity of 3,5‐diaryl pyrazolines in different cancer cell lines .…”
Section: Introductionmentioning
confidence: 99%
“…The pyrazole scaffold is a highly versatile drug-like template that is being used extensively in the design of cancer therapies [6,7], especially in the structure of various protein kinase inhibitors [8,9]. Some pyrazole derivatives progressed to clinical development, such as ruxolitinib, a selective JAK1 and JAK2 inhibitor approved for the treatment of myelofibrosis [10], crizotinib a c-Met and ALK inhibitor used in the treatment of non-small cell lung carcinoma [11], AT7519, an inhibitor of cyclin-dependent kinases used in refractory solid tumors [12], and tozasertib, a pan-Aurora kinase inhibitor [13].…”
Section: Introductionmentioning
confidence: 99%